A CFD study on wall shear stress of falling water film on food contact surface - Nawaporn Suthanarak; Navaphattra Nunak (My University, 2018)
This paper proposes a CFD model to simulate the wall shear stress of the falling water film on the hydrophilic surface (aluminum) of the inclined flat plate in the range of 30°, 60° and 90° at a flow rate of 100, 200 and 300 L/h. Wall shear stress simulated from the CFD using SST k-ω with the VOF model was compared with the real data obtained from the experiment. It was found that both inclined angle and water flow rate had an effect to the wall shear stress and the CFD with the proposed model had the potential to predict it with the maximum averaged error of 2.9%.
Keywords: Falling (accident); Fluid Dynamics and Thin Films